Assesment of platelet antiaggregant activity of the ethanolic fraction obtained from the bark of Nectandra amazonum Nees. - ESPITIA CORREDOR, Jenaro Antonio; CUCA SUÁREZ, Luis Enrique; GUERRERO PABÓN, Mario Francisco (Vitae, 2016)
Background: Some species of the Lauraceae family are known to produce secondary metabolites that have antiplatelet properties. Studies on the leaves of Nectandra amazonum Nees. have shown antiaggregant activity but the bark of this species has not been studied. Objectives: To assess the antiplatelet effect of the ethanolic fraction obtained from the bark of Nectandra amazonum Nees. [N.V. “laurel amarillo”, Lauraceae] applying the “Born” turbidimetric method. Methods: The screening test compared the effects of a fraction of N. amazonum (0.1 mg/mL), acetylsalicylic acid (ASA, 0.5 mM, as reference standard) and dimethylsulphoxide (DMSO, 0.1%, as control) on human platelets stimulated with adenosine diphosphate (ADP, 2 µM), epinephrine (EPI, 1 uM (one micromolar)), collagen (COLL, 1 µg/mL) and arachidonic acid (AA, 0.2 mg/mL). Subsequently, the study focused on determining the antiaggregant potency of the N. amazonum fraction through concentration - response curves (from 1 µg/mL to 0.4 mg/mL), obtaining pIC50 (-log IC50) values against the platelet agonists. Results: Control platelets attained the highest percentage values of aggregation (96% AA, 89% EPI, 85% COLL, and 77% ADP). The N. amazonum fraction significantly reduced the aggregation effects (6% AA, 45% EPI, 10% COLL, 21% ADP), with values close to those obtained with ASA (17% AA, 21% EPI, 10% COLL, 20% ADP). According to concentration - response curves, the pIC50 values of the ethanolic fraction indicated the following order of potency: AA, 4.90 > ADP, 4.51 > COLL, 4.33 > EPI, 3.85. Conclusions: These results suggest that the N. amazonum Nees. ethanolic fraction elicited antiplatelet effects mainly related to the inhibition of the arachidonic acid pathway.